2014
DOI: 10.1158/1055-9965.epi-13-1126
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation in Benign Prostate Tissue Is Associated with High-Grade Prostate Cancer in the Placebo Arm of the Prostate Cancer Prevention Trial

Abstract: Background Chronic inflammation is hypothesized to influence prostate cancer development, although a definitive link has not been established. Methods Prostate cancer cases (N=191) detected on a for-cause (clinically indicated) or end-of-study (protocol directed) biopsy, and frequency-matched controls (N=209), defined as negative for cancer on an end-of-study biopsy, were sampled from the placebo arm of the Prostate Cancer Prevention Trial. Inflammation prevalence and extent in benign areas of biopsy cores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
226
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(248 citation statements)
references
References 19 publications
15
226
6
1
Order By: Relevance
“…Inflammation is a response to internal and external environmental stimuli that functions to eliminate foreign agents and restore the physiology of normal tissue. However, when inflammation becomes chronic, it can result in the development of cancer (30,31). Inflammation following viral infection can drive the progression of cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a response to internal and external environmental stimuli that functions to eliminate foreign agents and restore the physiology of normal tissue. However, when inflammation becomes chronic, it can result in the development of cancer (30,31). Inflammation following viral infection can drive the progression of cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…13 Additionally, low chronic inflammations are also regarded to be one of the main reasons for the development of most age-related diseases like atherosclerosis, cardiovascular diseases, type 2 diabetes, Alzheimer's disease, and cancer. [14][15][16][17][18][19] Since nearly 20% of cancers are preceded by chronic inflammation, 20 the detection of early stages of inflammation is of particular importance.…”
mentioning
confidence: 99%
“…Because of infection, the shadowed and untreated acute inflammation could lead to chronic inflammation that subsequently results in changes in hormonal and metabolic states of males' body (1,17). Bashir in 2015 reported that the most common malignancy among males worldwide is the prostate cancer.…”
Section: Resultsmentioning
confidence: 99%